Typification of names in the genus Pinguicula L. (Lentibulariaceae) - Domínguez, Yoannis; Panfet Valdés, Cristina Mercedes; Miranda, Vitor Fernandes Oliveira (Phytotaxa, 2017)
Several names of the genus Pinguicula have been found to need typification or corrections to previous typifications. Analyses of original material and literature related to each name have led to the designation of 17 lectotypes, five neotypes and one epitype. Also five previously cited ‘holotypes’ were corrected to lectotypes. Notes discussing the selection or correction of type specimens are given for each name and, when possible, known isotypes are also cited.